Teorema de Hodge e aplicações - Ribeiro, Carlos Augusto David (2008)
This dissertation presents a classical theorem of decomposition of the space of smooths p-forms on compact oriented Riemannian manifold , known as the theorem of Hodge decomposition, and its consequences. During the same was made a passage for several interesting tools, such as Sobolev spaces(Chapter 2) and elliptical PDE (Chapter 3), as well as a succinct approach about diferenciable forms (Chapter 1).